Про концепцію розвитку Національної академії наук України на 2021—2025 роки - Богданов, В.Л.; Кубальський, О.Н. (Вісник НАН України, 2021)
У відповідь на нові виклики, які останнім часом постали перед академічною наукою, в поточному, 2021, році було прийнято нову Концепцію розвитку НАН України до 2025 року. У статті окреслено її головні принципи та цілі, спрямовані на посилення внеску Академії в реалізацію пріоритетних напрямів економічного та соціального розвитку держави, збільшення обсягу досліджень світового рівня, ефективне використання бюджетних коштів та майна, поліпшення ситуації з кадровим забезпеченням і налагодження тісніших зв’язків з владою та суспільством. The article presents the main results of the implementation of the tasks of the Concept of Development of the National Academy of Sciences of Ukraine for 2014-2021. It is noted that in response to the new challenges that the academic science has faced recently, in the current year, 2021, a new Concept of Development of the National Academy of Sciences of Ukraine until 2025 was adopted. Its main principles and goals, outlined in the article, are aimed at strengthening the Academy's contribution to the advancement of priority areas of economic and social development of the state, increasing world-class research, effective use of budget funds and property, improving the situation with staffing and establishing closer ties with the government and society.